Common atrium with single ventricle in a newborn: A case report - Akhigbe, I.E.; Bah, A.B. (SA Heart Journal, 2025)
The presence of a common atrium, a common atrioventricular valve in combination with a single ventricle, occurs very rarely, accounting for 1% - 2% of all congenital heart malformations. We report a rare case of a 21-day old male neonate diagnosed with a common atrium, single ventricle, a common atrioventricular valve and a patent ductus arteriosus. High index of suspicion and early diagnosis is vital for appropriate management and timely surgical interventions as required.